Copper current collectors reduce long-term fouling of air cathodes in microbial fuel cells. Issue 4 (16th February 2018) - Myung, Jaewook; Yang, Wulin; Saikaly, Pascal E.; Logan, Bruce E.
Abstract : Long-term operation of wastewater-fed, microbial fuel cells (MFCs) with cathodes made of activated carbon and stainless steel (SS) current collectors can result in decreased performance due to cathode fouling. Abstract : Long-term operation of wastewater-fed, microbial fuel cells (MFCs) with cathodes made of activated carbon and stainless steel (SS) current collectors can result in decreased performance due to cathode fouling. Copper has good antimicrobial properties, and it is more electrically conductive than SS. To demonstrate that a copper current collector could produce a more fouling resistant cathode, MFCs with air cathodes using either SS or copper current collectors were operated using domestic wastewater for 27 weeks. The reduction in biofouling over time was shown by less biofilm formation on the copper cathode surface compared to SS cathodes, due to the antimicrobial properties of copper. Maximum power densities from 17–27 weeks were 440 ± 38 mW m −2 using copper and 370 ± 21 mW m −2 using SS cathodes. The main difference in the microbial community was a nitrifying community on the SS cathodes, which was not present on the copper cathodes.